Death stalks all of us upon this earth! - Merrell, Neal (My University, 2015)
Type as Image: Eliciting Emotions is a project of DESN330 Typography II (Constanza Pacher + Carlos Fiorentino) in the Design Studies Diploma Program at MacEwan University. Students were asked to capture the essence of the book The Sisters Brothers by Patrick deWitt (MacEwan Book of the Year 2014/2015), and translate it into a three-poster series using typography as the main element. Under the premise that the visual form is dictated by the content, students were encouraged to analyze plot, characters, point of view, imagery, tone, themes and symbolism to extract key words, sentences and passages as the basis for their designs. Students were asked to challenge literal interpretations by exploring the use of expressive typography and text and image relationships.
Displayed March 4-31, 2015 at MacEwan University Library, City Centre Campus in Edmonton, Alberta.
Keywords: typography; poster design; The Sisters Brothers; Patrick deWitt; MacEwan Book of the Year